Dried blood spot cards: A reliable sampling method to detect human antibodies against rabies virus. - Laura Doornekamp; Carmen W E Embregts; Georgina I Aron; Simone Goeijenbier; David A M C van de Vijver; Eric C M van Gorp; Corine H GeurtsvanKessel (PLoS Neglected Tropical Diseases, 2020)
Background Although preventable by vaccination for more than a century, rabies virus still causes numerous fatalities every year. To determine antibody levels in humans, blood collected with a finger prick and applied on dried blood spot (DBS) cards is an alternative for venipuncture. The use of DBS is specifically valuable in remote areas, as it is easy to perform, store and transport. Therefore, the technique is frequently used for epidemiological studies of tropical diseases. Up to present, determination of rabies virus antibody levels on human DBS has not been validated. Methodology/principal findings We evaluated the use of human DBS for rabies serology and analyzed 99 pre- or post-vaccination serum and DBS samples with a fluorescent antibody virus neutralization test (FAVNt), which is the gold standard to detect protective antibody levels, and a Bio-Rad Platelia Rabies II ELISA. Sensitivity and specificity of DBS eluates tested with the FAVNt were 97% and 92%, respectively and 87% and 96% when tested with the Platelia-II ELISA. Antibody levels measured in serum with the FAVNt, correlated best with antibody levels measured in DBS with the FAVNt (R = 0.88). Conclusions/significance This is the first study that applies DBS for reliable detection of human antibodies against rabies virus. Both the FAVNt and Platelia-II ELISA demonstrate an acceptable performance on DBS, providing opportunities for rabies serology in remote areas. This technique could drastically ease studies evaluating (novel) rabies vaccination strategies and monitoring persisting immunity in humans at risk, living in rabies endemic regions.